1993
DOI: 10.1063/1.110304
|View full text |Cite
|
Sign up to set email alerts
|

Chemical vapor deposition of copper from Cu+1 precursors in the presence of water vapor

Abstract: Copper films have been deposited by low pressure chemical vapor deposition from mixtures of the Cu+1 precursor copper hexafluoroacetylacetonate vinyltrimethylsilane and water vapor. The addition of water vapor at the optimum concentration more than doubles the deposition rate and substantially reduces the nucleation time without adversely affecting the copper film resistivity, but excess amounts of water vapor significantly increase the copper resistivity. Auger electron spectroscopy analysis detects no impuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…In some previous studies of copper growth by CVD/ALD, water was used to enhance film nucleation and growth rate. [20][21][22][23] The addition of water was also found to have a large effect on copper film growth on the same substrate types as used in this study. 24 In this work, two different ALD sequences are applied, one including water ͓pulse sequence: Cu͑hfac͒ 2 /H 2 O/NH 3 ͔ and one without water ͓pulse sequence: Cu͑hfac͒ 2 /NH 3 ͔.…”
mentioning
confidence: 86%
“…In some previous studies of copper growth by CVD/ALD, water was used to enhance film nucleation and growth rate. [20][21][22][23] The addition of water was also found to have a large effect on copper film growth on the same substrate types as used in this study. 24 In this work, two different ALD sequences are applied, one including water ͓pulse sequence: Cu͑hfac͒ 2 /H 2 O/NH 3 ͔ and one without water ͓pulse sequence: Cu͑hfac͒ 2 /NH 3 ͔.…”
mentioning
confidence: 86%
“…Kim et al 17 also reported that shorter incubation times and enhanced growth rates could be achieved using water vapor. 7,17, 18 Mermet et al 7 reported that deposited film resistivity decreased upon annealing at 723 K for 30 min. Deposition for 30 min with water vapor flowing for the initial 30 s at 6.5 sccm resulted in pure copper films.…”
Section: Introductionmentioning
confidence: 99%
“…After copper nucleation by (2) or (3) in the case of Scheme 1, grain growth of copper will be continued on the nucleated copper as islands through the reaction (4) to (7). Therefore, the loss of selectivity reported in the literature(6) during copper CVD using Cu(H FA)(TMVS) may be closely related with the initial reaction of copper nucleation, i.e., the rate of disproportionation on the substrate and the rate of decomposition of Cu(HFA)(TMVS).…”
Section: Methodsmentioning
confidence: 99%